Effect of swedish massage on the quality of sleep of thalassemia beta major children - Ayu Yuliani S; Zaitun Zaitun (Science Midwifery, 2022)
The highest prevalence of thalassemia genes is found in certain tropical countries. This study aimed to determine the effect of Swedish massage on the sleep quality of children with beta-thalassemia. This study employed quasi-experimental research with a non-equivalent control group design before and after the experimental design. All thalassemia beta children treated at Gunung Jati Hospital in Cirebon were included in this study. This study employed the purposive sampling technique because the researcher determined the selection criteria for the sample. The results concluded that Swedish massage improved sleep quality in children with beta-thalassemia